The genre of the body of oral presentations delivered by english for workplace communication students - Seliman, Salbiah; Md. Naitm, Irwan Affendi (2010)
This research seeks to describe the moves of the body of oral presentations delivered by UTM Students enrolled in English for Workplace Communication. It also aims to determine the differences between the moves found in the body of oral presentations delivered by students in Faculty of Management and Human Resources Development and those delivered by students in Faculty of Education. The techniques used for obtaining data were videotaping and transcribing the oral presentations. The instruments used were transcribed oral presentations and Seliman’s (1996) checklist of moves of oral presentations. The findings of this research revealed that the students actually shared a set of similar moves in the body of their oral presentations. Differences observed were on the aspects of the utilization of moves that are unique by a certain group and the different strategies in setting the sequence of their moves. The non-linguistic differences discovered were found in the aim of presentation, knowledge on task, adequacy of information and structure of presentation.